2014
DOI: 10.1016/j.buildenv.2014.07.001
|View full text |Cite
|
Sign up to set email alerts
|

Integrated life-cycle assessment and thermal dynamic simulation of alternative scenarios for the roof retrofit of a house

Abstract: Building retrofit plays an important role in reducing environmental loads associated with the building stock. The main goal of this article is to perform a comprehensive energy and environmental lifecycle assessment (LCA) of the roof retrofit of a Portuguese single-family house integrating thermal dynamic simulation. A life-cycle model was developed to assess 27 alternative retrofit scenarios combining three types of insulation material (rock wool, extruded polystyrene and polyurethane foam), three insulation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
0
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(30 citation statements)
references
References 52 publications
(39 reference statements)
0
26
0
4
Order By: Relevance
“…Table 2 gives details of the opaque building envelope assemblies (roof, walls, floor and windows) characterized by their thermal parameters, such as heat transfer coefficient U and solar heat gain coefficient g w . The insulation thicknesses were selected based on previous studies [16], [38]. The thermal insulation material selected for this study was expanded polystyrene (EPS, with thermal conductivity of 0.036…”
Section: Historic Building: Model and Inventorymentioning
confidence: 99%
See 1 more Smart Citation
“…Table 2 gives details of the opaque building envelope assemblies (roof, walls, floor and windows) characterized by their thermal parameters, such as heat transfer coefficient U and solar heat gain coefficient g w . The insulation thicknesses were selected based on previous studies [16], [38]. The thermal insulation material selected for this study was expanded polystyrene (EPS, with thermal conductivity of 0.036…”
Section: Historic Building: Model and Inventorymentioning
confidence: 99%
“…LCA methodology has been applied to assess the environmental impacts of building retrofit actions [11][12][13][14][15][16]. This approach has also been applied to redesign the concept of NZEB with the aim of reaching an electricity target of net zero energy assuming that these type of buildings can heavily be influenced by the energy carrier weighting factors chosen [17].…”
Section: Introductionmentioning
confidence: 99%
“…The authors concluded that, for typical climatic conditions of southern Europe, it is possible to significantly improve the thermal efficiency of residential buildings by increasing the insulation level of the weaker components of the building envelope without significantly increasing the embodied energy of the building. Rodrigues and Freire [227] also carried out a LCA study focusing on the retrofitting of a roof of a residential building and taking into account the balance between the embodied energy and the operational energy of the building over its service life. The authors concluded that after a certain level of insulation, the increase of the insulation layer would not compensate the increase of the embodied energy.…”
Section: Balance Between Embodied Energy and Operational Energymentioning
confidence: 99%
“…For example, the environmental impact of different structural retrofit techniques such as steel jacketing and fiber-reinforced polymer retrofit has been analyzed by Moliner et al (2013), Zhang et al (2012), and Das (2011). Other studies focused on the environmental impact of different structural options such as flat roof, floor on grade, and the integration of green roof in existing buildings (Rodrigues and Freire 2014;Perini 2013;Allacker 2012).…”
mentioning
confidence: 97%